Réponses

2013-10-13T16:37:38+02:00
2013-10-13T17:06:15+02:00
8*(a+3)* 5*(a-1)* 3*(2+x) *4*(3-b) = ( 8a + 24 ) *( 5a - 5 ) * ( 6 + 3x ) * ( 12 - 4b )
                                       = ( 40a² - 40a + 120a - 120 ) * ( -24b + 72 - 12bx + 36x )
 = -960a²b + 2880a² - 480a²bx + 1360a²x + 960ab - 2880a + 480axb - 1360ax - 2880ab + 8640a - 1440abx + 4320ax + 2880b - 8640 + 1440bx - 4320x 
= - 960a²b + 2880a² - 480a²bx + 1360a²x - 1920ab + 5760a - 960abx + 2960ax + 2880b + 1440bx - 8640 - 4320x

Presque sure que c'est ça !